Prevention of the toxic effect of uranium on bone formation by tetracycline - Cabrini, Rómulo Luis; Guglielmotti, M. B.; Ubios, Angela M. (1984)
Fil: Cabrini, Rómulo Luis Comisión Nacional de Energía Atómica; Argentina